Atrial fibrillation occurring transiently with stress. (January 2018) - McIntyre, William F.; Connolly, Stuart J.; Healey, Jeff S.
Abstract : Purpose of review: Atrial fibrillation may be detected in the setting of an acute stressor, such as medical illness or surgery. It is uncertain if atrial fibrillation detected in these settings (AFOTS: atrial fibrillation occurring transiently with stress) is secondary to a reversible trigger or is simply paroxysmal atrial fibrillation. This distinction is critical for clinicians, who must decide if AFOTS can be dismissed as a reversible phenomenon, or if it signals the need for chronic therapy; in particular, anticoagulation. Recent findings: Published studies report incidences of AFOTS ranging from 1 to 44% in patients with acute medical illness and 1 to 35% following noncardiac surgery. The highest estimates have been reported in critically ill patients and in those undergoing continuous monitoring. A small number of studies have reported the recurrence of atrial fibrillation after AFOTS to be 55–68% within 5 years of medical illness and 37% within 1 year after noncardiac surgery. These studies are limited by retrospective design and low-sensitivity ascertainment. Summary: AFOTS commonly occurs in patients with acute medical illness or in the postoperative state, and atrial fibrillation recurs in over 50% of individuals. Prospective postdischarge studies using sensitive atrial fibrillation detection strategies are needed to define the relationship between AFOTS and clinical atrial fibrillation.